Յովհան Մայրագոմեցու երրորդութենաբանական եւ քրիստոսաբանական հայեացքների շուրջ - Եզեկյան, Տ. Անդրէաս Վրդ․ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Иоанн (Ован) Майрагомеци — один из важнейших деятелей и богословов VII в., с именем которого традиционно связано появление и распространение в Армянской Церкви ереси афтартодокетизма. Несмотря на это важное обстоятельство, до сих пор его богословские взгляды не подвергались тщательному исследованию. В данной статье в основном рассматриваются взгляды Иоанна Майрагомеци на христологию и учение о Св. Троице. Hovhan of Mayragom is one of the renowned figures and theologians of the Armenian Church of the 7th century, whose name is traditionally associated with the origin and spread of Aphthartodocetism in the Armenian Church. Despite this important fact, his theological views have not yet been thoroughly studied. In this article, the subject of examination is mainly the Trinitarian and Christological views of Hovhan of Mayragom. Considering his Trinitarian views, it should be clearly emphasized that he does not go beyond the framework of the Orthodox doctrine on the Holy Trinity. However, the terms used by him were not clear enough and thus caused him to be accused of supporting Sabellianism (Modalistic Monarchianism). In terms of his Christological views, it should be noted that he no way questioned the fact of the Incarnation of Jesus Christ; however, by denying the existence of certain human qualities in the Lord, he questioned the fact that He was a perfect human being․
Keywords: Religion